Incidence and Etiology of Surgical Site Infections among Emergency Postoperative Patients in Mbarara Regional Referral Hospital, South Western Uganda - Lubega, Abubaker; Joel, Bazira; Lucy, Najjuka Justina (Surgery research and practice, 2017)
Background: This prospective hospital based study was conducted to determine the incidence, risk factors, and causative agents of surgical site infection their susceptibility to among 114 emergency postoperative patients at the Mbarara Regional Referral Hospital between September 2014 and January 2015. Methods: Consented patients were consecutively enrolled and their preoperative, intraoperative, and postoperative data were collected. Follow-ups were done in the surgical outpatient clinics. Wound specimens were collected and processed as per Sops; susceptibility testing was done using the Kirby-Bauer disc diffusion technique. Data was analyzed using STATA 11.0. Results: Overall SSI incidence was 16.4%: 5.9% superficial and 47.1% deep and organ space SSIs each. Klebsiella pneumoniae was the most predominant organism (50%) followed by Staphylococcus aureus (27.8%). E. coli and P. aeruginosa both accounted for 11.1%. Wound class (𝑝 = 0.009), anaemia (𝑝 = 0.024), low serum albumin (𝑝 = 0.046), and property of suture material used (𝑝 = 0.006) were significantly associated with SSIs. All organisms had 100% resistance to ampicillin, tetracycline, septrin, and erythromycin. Ciprofloxacin and ceftriaxone are highly sensitive to all organisms Conclusion: The incidence of SSI in this hospital is very high. Klebsiella pneumoniae is the predominant cause. Ciprofloxacin are very potent
Keywords: Surgical Site Infections; Incidence and Etiology; Emergency Postoperative Patients; Uganda